1989
DOI: 10.1182/blood.v73.6.1635.1635
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal noncutaneous lymphoid hyperplasias represent a continuous spectrum of B-cell neoplasia: demonstration by molecular genetic analysis

Abstract: We investigated 16 lymphoid proliferations occurring in the ocular adnexa, salivary glands, breast, and thyroid gland and satisfying the histopathologic and immunophenotypic criteria of benign lymphoid hyperplasia for the presence of clonal rearrangements of the antigen receptor, c-myc, bcl-1, and bcl-2 genes and Epstein-Barr virus (EBV) DNA sequences. Each of these 16 extranodal, noncutaneous lymphoid neoplasms exhibited clonal immunoglobulin heavy and/or light chain and lacked T-cell receptor (TCR) beta-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…According to Wan et aI., monoclonality was detected in 92% of cases of B cell non-Hodgkin's lymphoma and was relatively specific for this disease. On the other hand, rearrangements of immunoglobulin genes have been reported in some inflammatory and neoplastic conditions (lymphadenopathy in transplant patients (8), orbital pseudotumors (9), Sjogren syndrome (10), and so on). According to these clinical examples, demonstration of gene rearrangement by itself may not be sufficient for a diagnosis of malignancy, but it may indicate an abnormal lymphoproliferative process in which a substantial proportion of cells represent a single clone.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wan et aI., monoclonality was detected in 92% of cases of B cell non-Hodgkin's lymphoma and was relatively specific for this disease. On the other hand, rearrangements of immunoglobulin genes have been reported in some inflammatory and neoplastic conditions (lymphadenopathy in transplant patients (8), orbital pseudotumors (9), Sjogren syndrome (10), and so on). According to these clinical examples, demonstration of gene rearrangement by itself may not be sufficient for a diagnosis of malignancy, but it may indicate an abnormal lymphoproliferative process in which a substantial proportion of cells represent a single clone.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 This has prompted the suggestion that reactive lymphoid hyperplasia is an unstable lesion leading to development of progressive clonal expansions of B-lymphocytes within the orbit with the potential to result in malignant lymphoma. 3 This is believed to be the result of an immunoregulatory defect in which T-helper cells outnumber the T-suppressor cells. 3 Most orbital adnexal tumours present with palpable mass, proptosis or ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 This is believed to be the result of an immunoregulatory defect in which T-helper cells outnumber the T-suppressor cells. 3 Most orbital adnexal tumours present with palpable mass, proptosis or ptosis. Irrespective of the pathology, staging investigations are recommended at diagnosis as the extent of the disease is a strong determinant of prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using these methods have demonstrated that ocular adnexal lymphoid proliferations may represent a continuous spectrum of B cell lymphocyte neoplasms ranging from polymorphic lesions harboring small monoclonal B-cell lymphocyte populations to monomorphic malignant lymphomas comprised almost entirely of a single clonal B cell population. 2,3,16,17 We present here a study of six lacrimal gland lymphomas studied by fine-needle aspiration cytology, flow cytometric immunophenotyping, and gene rearrangement studies. There have been only a few cytomorphologic studies of ocular adnexal lymphoid proliferations 4-8 and no studies specifically addressing the cytologic features of lacrimal gland lymphomas.…”
mentioning
confidence: 99%